Grazing incidence X‐ray fluorescence analysis of buried interfaces in periodically structured crystalline silicon thin‐film solar cells. Issue 3 (2nd March 2015) - Eisenhauer, David; Pollakowski, Beatrix; Baumann, Jonas; Preidel, Veit; Amkreutz, Daniel; Rech, Bernd; Back, Franziska; Rudigier‐Voigt, Eveline; Beckhoff, Burkhard; Kanngieβer, Birgit; Becker, Christiane
Abstract : We present grazing incidence X‐ray fluorescence (GIXRF) experiments on 3D periodically textured interfaces of liquid phase crystallized silicon thin‐film solar cells on glass. The influence of functional layers (SiO x or SiO x /SiC x ) – placed between glass substrate and silicon during crystallization – on the final carbon and oxygen contaminations inside the silicon was analyzed. Baring of the buried structured silicon surface prior to GIXRF measurement was achieved by removal of the original nano‐imprinted glass substrate by wet‐chemical etching. A broad angle of incidence distribution was determined for the X‐ray radiation impinging on this textured surface. Optical simulations were performed in order to estimate the incident radiation intensity on the structured surface profile considering total reflection and attenuation effects. The results indicate a much lower contamination level for SiO x compared to the SiO x /SiC x interlayers, and about 25% increased contamination when comparing structured with planar silicon layers, both correlating with the corresponding solar cell performances.